“A passion to change the landscape and drive a renaissance”: The mRNA Hub at Afrigen as decolonial aspiration - Paremoer, Lauren; Pollock, Anne (Frontiers in Public Health, 2022)
In global conversations about Covid vaccine access, Africa has overwhelmingly been characterised as a site of lack. However, the successful reverse engineering of the Moderna vaccine by Afrigen at the mRNA Hub in Cape Town marks a more hopeful path forward. This paper introduces the mRNA Hub and puts it into context of broader decolonial aspirations for African futures in the face of rich countries’ disregard. Highlighting ways in which Afrigen’s Managing Director’s articulations of the endeavour resonate with historical and contemporary calls to dismantle the unequal global order, we argue that the mRNA Hub provides an example of the potential for decolonial solidarity in the post/pandemic period.